Goddesses in the Synagogue? - Xeravits, Géza G. (Journal for the study of Judaism, 2017)
This note deals with two panels of the west wall of the Dura synagogue, the details of which were interpreted by some scholars as probably connected to depictions of goddesses. Close investigation of these details, however, does not substantiate this view. The images, both in themselves and as parts of a larger composition, need not be interpreted as displaying conscious allusions to pagan female divinities.